2023
DOI: 10.1128/spectrum.02618-22
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Tannic Acid In Vitro and Its Protective Effect on Mice against Clostridioides difficile

Abstract: Clostridioides difficile is one of the major pathogens to cause antibiotic-associated diarrhea. Although antibiotic treatment is still the most commonly used and effective treatment for CDI, the destruction of indigenous intestinal microbiota by antibiotics is the main reason for the high CDI recurrence rate of about 20%, which is increasing every year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In particular, tannic acid may lead to improved antibacterial activity by disturbing the uptake of sugars and amino acids, restricting bacterial growth. According to Wang et al, tannic acid inhibits the growth of Clostridioides difficile strains at concentrations above 16 g/mL [61]. Gullon et al, and Qi et al, reported that rutin and quercetin possess antimicrobial efficacy [62,63].…”
Section: Resin Extractsmentioning
confidence: 99%
“…In particular, tannic acid may lead to improved antibacterial activity by disturbing the uptake of sugars and amino acids, restricting bacterial growth. According to Wang et al, tannic acid inhibits the growth of Clostridioides difficile strains at concentrations above 16 g/mL [61]. Gullon et al, and Qi et al, reported that rutin and quercetin possess antimicrobial efficacy [62,63].…”
Section: Resin Extractsmentioning
confidence: 99%
“…Of these, Galla chinensis tannic acid (GCTA) is a hydrolysable tannin representing at least 70% of its total weight [ 16 ]. GCTA has been found to inhibit bacterial growth [ 17 ], modulate host immune responses [ 18 ], improve intestinal barrier function [ 11 ] and influence the gut microbiota [ 19 ]. GCTA has demonstrated anti-virulence by targeting the type III secretion system against Salmonella [ 20 ].…”
Section: Introductionmentioning
confidence: 99%